Expanding the Application of EFQM model for Institutional Accreditation of Educational Organizations - Yskak, Nabi (Advances in Social Sciences Research Journal, 2021)
Relevance of this article topic consists in the necessity to find some alternative to the existing practice of using of the 2015 Standards and Guidelines for Quality Assurance in the EHEA (ESG-15) for accreditation of educational organizations in Kazakhstan. This study purpose is to develop the ways of expanding the European Foundation for Quality Management (EFQM) use for institutional accreditation of universities. Methods: comparativ analysis, formalization method. Results: 1) the genesis, functions and levels of educational organizations’ accreditation in Kazakhstan are described; 2) existence of the link between EFQM and ESG-15 is proved, however, EFQM is more adapted to institutional accreditation of higher education institutions; and 3) it is shown if formalized data are used to prescribe the scores when filling in the RADAR matrix, then filling in the RADAR matrix will be easier, and subjectivity will decrease, and accuracy will increase.